A Paradigmatic Reconstruction of the National Curriculum through a Holistic Multidimensional Education Framework - Jaja Jamaludin; Muhammad Sahal (Journal of Pedagogi, 2026)
Contemporary educational systems face unprecedented challenges including persistent learning crises, curriculum fragmentation, and instructional practices that prioritize cognitive outcomes while marginalizing emotional, social, spiritual, aesthetic, and ecological dimensions of human development. This study proposes a paradigmatic reconstruction of national curricula through a theoretically grounded and pedagogically actionable Holistic Multidimensional Education Framework that operationalizes comprehensive human development.  Employing a qualitative conceptual design, this research conducted a systematic narrative literature review of 30 peer-reviewed international studies published between 2020 and 2025. Thematic analysis identified patterns, gaps, and convergences across holistic education theory, curriculum design, instructional methodologies, and sustainability education. Findings reveal that conventional curriculum paradigms inadequately address multidimensional learner development, resulting in fragmented educational experiences disconnected from authentic contexts. The proposed framework integrates six developmental dimensions cognitive, emotional, social, spiritual, aesthetic, and ecological operationalized through Project-Based Learning (PjBL) and Experiential Learning as core instructional strategies. This framework provides actionable pathways for curriculum reform by bridging holistic education theory with instructional design, offering implications for policy development, teacher preparation, and alignment with Sustainable Development Goals.